Municipal Incorporation Activity in the United States Patterns, People and Procedures - Smith, Russell M. (The Urban Book Series,, 2018)
This book provides a comprehensive analysis of the municipal incorporation activity in the United States over the last several decades and the geographic consequences of the incorporation of new cities. It aims to explore new municipalities and to develop a better understanding and appreciation for these complex local government boundary changes. Since 1990, the United States has witnessed the incorporation of more than 400 new cities. These newly incorporated municipalities (NIMs) were established on the edges of growing metropolitan areas, in beach and mountain resort destinations, and largely rural counties. The incorporation of these new cities is a complex and politically charged geographic event. These new cities can contribute to metropolitan fragmentation within a region, provide important public services to growing urban areas, and/or exclude unwanted populations. New cities can also result in new school boundaries, new levels of taxation, and new boards and commissions with varied political powers. .